Pneumonia case-finding in the RESPIRE Guatemala indoor air pollution trial: standardizing methods for resource-poor settings - Nigel Bruce; Martin Weber; Byron Arana; Anaite Diaz; Alisa Jenny; Lisa Thompson; John McCracken; Mukesh Dherani; Damaris Juarez; Sergio Ordonez; Robert Klein; Kirk R Smith (The World Health Organization, 2007)
OBJECTIVE: Trials of environmental risk factors and acute lower respiratory infections (ALRI) face a double challenge: implementing sufficiently sensitive and specific outcome assessments, and blinding. We evaluate methods used in the first randomized exposure study of pollution indoors and respiratory effects (RESPIRE): a controlled trial testing the impact of reduced indoor air pollution on ALRI, conducted among children < 18 months in rural Guatemala. METHODS: Case-finding used weekly home visits by fieldworkers trained in integrated management of childhood illness methods to detect ALRI signs such as fast breathing. Blindness was maintained by referring cases to study physicians working from community centres. Investigations included oxygen saturation (SaO2), respiratory syncytial virus (RSV) antigen test and chest X-ray (CXR). FINDINGS: Fieldworkers referred > 90% of children meeting ALRI criteria, of whom about 70% attended a physician. Referrals for cough without respiratory signs and self-referrals contributed 19.0% and 17.9% of physician-diagnosed ALRI cases respectively. Intervention group attendance following ALRI referral was 7% higher than controls, a trend also seen in compliance with RSV tests and CXR. There was no evidence of bias by intervention status in fieldworker classification or physician diagnosis. Incidence of fieldworker ALRI (1.12 episodes/child/year) is consistent with high sensitivity and low specificity; incidence of physician-diagnosed ALRI (0.44 episodes/child/year) is consistent with comparable studies. CONCLUSION: The combination of case-finding methods achieved good sensitivity and specificity, but intervention cases had greater likelihood of reaching the physician and being investigated. There was no evidence of bias in fieldworkers' classifications despite lack of concealment at home visits. Pulse oximetry offers practical, objective severity assessment for field studies of ALRI.